White Hunter Black Heart - Eastwood, Clint; Cornwell, Charlotte; Edward TudorPole; George Dzundza; Jeff Fahey; Norman Lumsden; Roddy MaudeRoxby; Clint Eastwood (USA Malpaso Productions, 1990)
The world famous movie director John Huston has gone to Africa to make his next movie. He is an obstinate, contrary director who'd rather hunt elephants than takes care of his crew or movie. He has become obsessed with one particular elephant and cares for nothing else.
A thinly fictionalized account of a legendary movie director, whose desire to hunt down an animal turns into a grim situation with his movie crew in Africa.
Peter Viertel
Languages: English, French, German, Italian, Spanish
Subtitles: English, French, German, Italian, Spanish, Nederlands, Arabic, Czech, Dansk, Suomi, Hindi, Magyar, Islenka, Norsk, Polish, Portuguese, Svenska, Turkish
Keywords: Action; Drama; Adventure